2021
DOI: 10.15829/1728-8800-2021-2539
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity in chronic obstructive pulmonary disease and cardiovascular disease

Abstract: Comorbidity is one of the most significant problems of modern healthcare. Numerous studies have analyzed the possible pathogenetic mechanisms and relationships between a wide variety of diseases. Cardiovascular (CVD) and pulmonary diseases, in particular chronic obstructive pulmonary disease (COPD), have a number of the same risk factors and pathogenetic links, which aggravate each other's course. Moreover, CVD and COPD are among the most common diseases in the world. This review provides up-to-date informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
11

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 46 publications
0
21
0
11
Order By: Relevance
“…It is assumed that in nonmassive PE, reversible damage of RV cardiomyocytes and release of cytosolic troponins pool through the cell membrane due to increased afterload occur. 86,87 In submassive and massive PE, RV overload is much more pronounced and cardiomyocyte necrosis develops. Probably the cause of cardiac myocyte necrosis in PE are sharp overload and expansion of RV, which might lead to compression of small branches of coronary arteries, passing in myocardial tissue thickness, causing disruption of hemoperfusion and delivery of oxygen and metabolic substrates to myocardial cells.…”
Section: Cardiac Troponins In Pulmonary Embolism: Diagnostic Value and Mechanisms Of Elevationmentioning
confidence: 99%
“…It is assumed that in nonmassive PE, reversible damage of RV cardiomyocytes and release of cytosolic troponins pool through the cell membrane due to increased afterload occur. 86,87 In submassive and massive PE, RV overload is much more pronounced and cardiomyocyte necrosis develops. Probably the cause of cardiac myocyte necrosis in PE are sharp overload and expansion of RV, which might lead to compression of small branches of coronary arteries, passing in myocardial tissue thickness, causing disruption of hemoperfusion and delivery of oxygen and metabolic substrates to myocardial cells.…”
Section: Cardiac Troponins In Pulmonary Embolism: Diagnostic Value and Mechanisms Of Elevationmentioning
confidence: 99%
“…The mechanisms of increasing cardiac troponins in non-massive PE are most likely associated with the release of the cytosolic pool through the membrane of the right ventricular cardiomyocytes, due to increased afterload, which is similar to how it occurs during intense physical exertion [67][68][69]. In the case of submassive and massive PE, necrosis of cardiomyocytes happens.…”
Section: Diagnostic Valuae and Mechanisms Of Elevation In Cardiac Troponins In Pementioning
confidence: 90%
“…It has been shown that the heart rate, blood pressure, vascular resistance, prothrombotic tendency, platelet aggregation ability, activity of the renin-angiotensin-aldosterone system, activity of the sympathoadrenal system, and levels of catecholamines and cortisol increase in the morning hours, which have evolved and are necessary for normal functioning in the period of wakefulness. However, this has important implications for the pathophysiology of cardiovascular diseases: the frequency of cardiovascular accidents is significantly higher in the morning hours [113][114][115][116][117][118]. The maximum number of cases of AMI occurs in the morning-afternoon time interval (8:00-12:00).…”
Section: Circadian Aspects On the Cardiac Troponins Concentration Fluctuationsmentioning
confidence: 99%